Construction of a 0D/1D composite based on Au nanoparticles/CuBi2O4 microrods for efficient visible-light-driven photocatalytic activity - Shi, Weilong; Li, Mingyang; Ren, Hongji; Guo, Feng; Huang, Xiliu; Shi, Yu; Tang, Yubin (Beilstein Journal of Nanotechnology, 2019)
Photocatalysis is considered to be a promising technique for the degradation of organic pollutants. Herein, a 0D/1D composite photocatalyst consisting of Au nanoparticles (NPs) and CuBi2O4 microrods (Au/CBO) was designed and prepared by a simple thermal reduction–precipitation approach. It shows excellent photocatalytic performance in the degradation of tetracycline (TC). The maximum photocatalytic degradation rate constant for Au/CBO composites with 2.5 wt % Au NPs was 4.76 times as high as that of bare CBO microrods. Additionally, the 0D/1D Au/CBO composite also exhibited ideal stability. The significant improvement of the photocatalytic performance could be attributed to the improved light harvesting and increased specific surface area, enhancing photoresponse and providing more active sites. Our work shows a possible design of efficient photocatalysts for environmental remediation.
Keywords: Au nanoparticles; 0D/1D composite; CuBi2O4 microrods; photocatalysis; photocatalytic degradation

(untitled) - Liu, Y.; Kong, J.; Yuan, J.; Zhao, W.; Zhu, X.; Sun, C.; Xie, J. (Chem. Eng. J., 2018)

(untitled) - Deng, F.; Zhao, L.; Luo, X.; Luo, S.; Dionysiou, D. D. (Chem. Eng. J., 2018)

(untitled) - Lu, Z.; Yu, Z.; Dong, J.; Song, M.; Liu, Y.; Liu, X.; Ma, Z.; Su, H.; Yan, Y.; Huo, P. (Chem. Eng. J., 2018)

(untitled) - Jiang, L.; Yuan, X.; Zeng, G.; Liang, J.; Chen, X.; Yu, H.; Wang, H.; Wu, Z.; Zhang, J.; Xiong, T. (Appl. Catal., B, 2018)

(untitled) - Jo, W. J.; Kang, H. J.; Kong, K.-J.; Lee, Y. S.; Park, H.; Lee, Y.; Buonassisi, T.; Gleason, K. K.; Lee, J. S. (Proc. Natl. Acad. Sci. U. S. A., 2015)

(untitled) - Wu, X.; Zhao, J.; Guo, S.; Wang, L.; Shi, W.; Huang, H.; Liu, Y.; Kang, Z. (Nanoscale, 2016)

(untitled) - Tian, J.; Sang, Y.; Yu, G.; Jiang, H.; Mu, X.; Liu, H. (Adv. Mater. (Weinheim, Ger.), 2013)

(untitled) - Liang, J.; Liu, F.; Deng, J.; Li, M.; Tong, M. (Water Res., 2017)

(untitled) - Qu, X.; Liu, M.; Yang, J.; Wang, C.; Meng, H.; Li, S.; Shi, L.; Du, F. (J. Solid State Chem., 2018)

(untitled) - Wang, P.; Xu, L.; Ao, Y.; Wang, C. (J. Colloid Interface Sci., 2017)

(untitled) - Shi, W.; Guo, F.; Yuan, S. (Appl. Catal., B, 2017)

(untitled) - Shi, W.; Guo, F.; Li, M.; Shi, Y.; Wu, M.; Tang, Y. (J. Alloys Compd., 2019)

(untitled) - Elaziouti, A.; Laouedj, N.; Bekka, A. (Environ. Sci. Pollut. Res., 2016)

(untitled) - Oh, W.-D.; Lua, S.-K.; Dong, Z.; Lim, T.-T. (Nanoscale, 2015)

(untitled) - Sharma, G.; Zhao, Z.; Sarker, P.; Nail, B. A.; Wang, J.; Huda, M. N.; Osterloh, F. E. (J. Mater. Chem. A, 2016)

(untitled) - Liu, Y.; Chen, Y.; Zhou, W.; Jiang, B.; Zhang, X.; Tian, G. (Catal. Sci. Technol., 2018)

(untitled) - Naik, G. K.; Majhi, S. M.; Jeong, K.-U.; Lee, I.-H.; Yu, Y. T. (J. Alloys Compd., 2019)

(untitled) - Wang, M.; Ye, M.; Iocozzia, J.; Lin, C.; Lin, Z. (Adv. Sci., 2016)

(untitled) - Liu, S.; Tang, Z.-R.; Sun, Y.; Colmenares, J. C.; Xu, Y.-J. (Chem. Soc. Rev., 2015)

(untitled) - Meng, S.; Cui, Y.; Wang, H.; Zheng, X.; Fu, X.; Chen, S. (Dalton Trans., 2018)

(untitled) - Chen, Z.; Feng, C.; Li, W.; Sun, Z.; Hou, J.; Li, X.; Xu, L.; Sun, M.; Bu, Y. (Chin. J. Catal., 2018)

(untitled) - Wang, J.; Wang, Z.; Li, L.; Chen, J.; Zheng, J.; Jia, S.; Zhu, Z. (RSC Adv., 2017)

(untitled) - Jia, J.; Du, X.; Liu, E.; Wan, J.; Pan, C.; Ma, Y.; Hu, X.; Fan, J. (J. Phys. D: Appl. Phys., 2017)

(untitled) - Yan, X.; Zhu, X.; Li, R.; Chen, W. (J. Hazard. Mater., 2016)

(untitled) - Zeng, J.; Song, T.; Lv, M.; Wang, T.; Qin, J.; Zeng, H. (RSC Adv., 2016)

(untitled) - Jia, Y.; Ma, H.; Liu, C. (Appl. Surf. Sci., 2019)

(untitled) - Liu, C.-J.; Yang, T.-Y.; Wang, C.-H.; Chien, C.-C.; Chen, S.-T.; Wang, C.-L.; Leng, W.-H.; Hwu, Y.; Lin, H.-M.; Lee, Y.-C.; Cheng, C.-L.; Je, J. H.; et al. (Mater. Chem. Phys., 2009)

(untitled) - Guo, F.; Shi, W.; Wang, H.; Huang, H.; Liu, Y.; Kang, Z. (Inorg. Chem. Front., 2017)

(untitled) - Ge, M.; Zhu, N.; Zhao, Y.; Li, J.; Liu, L. (Ind. Eng. Chem. Res., 2012)

(untitled) - Chen, X.; Dai, Y.; Guo, J. (Mater. Lett., 2015)

(untitled) - Najafian, H.; Manteghi, F.; Beshkar, F.; Salavati-Niasari, M. (J. Hazard. Mater., 2019)

(untitled) - Zhu, X.; Guan, Z.; Wang, P.; Zhang, Q.; Dai, Y.; Huang, B. (Chin. J. Catal., 2018)

(untitled) - Xu, N.; Li, F.; Gao, L.; Hu, H.; Hu, Y.; Long, X.; Ma, J.; Jin, J. (ACS Sustainable Chem. Eng., 2018)

(untitled) - Xu, N.; Li, F.; Gao, L.; Hu, H.; Hu, Y.; Long, X.; Ma, J.; Jin, J. (Int. J. Hydrogen Energy, 2018)

(untitled) - Wang, F.; Yang, H.; Zhang, Y. (Mater. Sci. Semicond. Process., 2018)

(untitled) - Hezam, A.; Namratha, K.; Drmosh, Q. A.; Ponnamma, D.; Nagi Saeed, A. M.; Ganesh, V.; Neppolian, B.; Byrappa, K. (J. Mater. Chem. A, 2018)

(untitled) - Samanta, S.; Martha, S.; Parida, K. (ChemCatChem, 2014)

(untitled) - Shi, W.; Guo, F.; Li, M.; Shi, Y.; Shi, M.; Yan, C. (Appl. Surf. Sci., 2019)

(untitled) - Li, M.-y.; Tang, Y.-b.; Shi, W.-l.; Chen, F.-y.; Shi, Y.; Gu, H.-c. (Inorg. Chem. Front., 2018)

(untitled) - Teng, W.; Tan, X.; Li, X.; Tang, Y. (Appl. Surf. Sci., 2017)

(untitled) - Ji, Z.; Feng, L.; Kong, L.; Shen, X.; Wang, J.; Xu, K.; Yue, X. (J. Mater. Sci., 2017)

(untitled) - Wang, X.; Yan, J.; Ji, H.; Chen, Z.; Xu, Y.; Huang, L.; Zhang, Q.; Song, Y.; Xu, H.; Li, H. (SpringerPlus, 2016)

(untitled) - Yang, H.; Wang, Y.; Nie, Y.; Sun, S.; Yang, T. (J. Compos. Mater., 2017)